Start by finding the slope using m = (y2 - y1)/(x2 - x1). Substituting in you get (-1 + 3)/(6 - 3). So m = 2/3
Next, use y - y1 = m(x - x1) and substitute any of the coordinates in: y + 3 = 2/3(x - 3). That gives you y + 3 = (2/3)x - 2. So tha final answer is y = (2/3)x -5
Answer:
6
Step-by-step explanation:
15.50 x 6= 93 and 100-7=93 therefor its 6
64, 45, 53 I think if I’m wrong don’t be mad haha
Two column proofs are organized into statement and reason columns. Each statement must be justified in the reason column. The
reason column will typically include "given", vocabulary definitions, and theorems.
Therefore, w<span>hat can be used as a reason in a two-column proof are:
Postulates
Definitions</span>